2020
DOI: 10.1002/jbmr.3995
|View full text |Cite
|
Sign up to set email alerts
|

Adult Osteosclerotic Metaphyseal Dysplasia With Progressive Osteonecrosis of the Jaws and Abnormal Bone Resorption Pattern Due to a LRRK1 Splice Site Mutation

Abstract: Osteosclerotic metaphyseal dysplasia (OSMD) is a rare autosomal recessive sclerosing skeletal dysplasia. We report on a 34-year-old patient with sandwich vertebrae, platyspondyly, osteosclerosis of the tubular bones, pathologic fractures, and anemia. In the third decade, he developed osteonecrosis of the jaws, which was progressive in spite of repeated surgical treatment over a period of 11 years. An iliac crest bone biopsy revealed the presence of hypermineralized cartilage remnants, large multinucleated oste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Recent structural work reveals that the C-terminal 28 residues of LRRK2 form an elongated α-helix that extends along the entire kinase domain, interacting with both its C-and N-lobes that likely stabilize the kinase domain and may form binding platforms for other LRRK2 regulators [59]. Several autosomal recessive variants that induce frameshift or truncating mutations impact the equivalent C-terminal residues of LRRK1 and cause OSMD [6][7][8][9]. We have found that one of these mutations, namely E1980A-FS, impacts the C-terminal 66 residues and inactivates LRRK1 (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent structural work reveals that the C-terminal 28 residues of LRRK2 form an elongated α-helix that extends along the entire kinase domain, interacting with both its C-and N-lobes that likely stabilize the kinase domain and may form binding platforms for other LRRK2 regulators [59]. Several autosomal recessive variants that induce frameshift or truncating mutations impact the equivalent C-terminal residues of LRRK1 and cause OSMD [6][7][8][9]. We have found that one of these mutations, namely E1980A-FS, impacts the C-terminal 66 residues and inactivates LRRK1 (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence in humans, points towards LRRK1 regulating bone biology and LRRK2 contributing to Parkinson's disease. Autosomal recessive variants that induce frameshift or truncating mutations within the C-terminal domain of LRRK1, that are likely loss of function, cause a severe metabolic bone disorder termed osteosclerotic metaphyseal dysplasia (OSMD) [6][7][8][9]. This is a unique form of osteopetrosis characterized by severe osteosclerosis localized to the metaphyses of long bones [10].…”
Section: Introductionmentioning
confidence: 99%
“…Extremely rare forms of osteoclast-rich osteopetrosis are caused by defects in the carbonic anhydrase 2 ( CA2 ) ( Sly et al, 1983 ), pleckstrin homology and RUN domain-containing M1 ( PLEKHM1 ) ( Van Wesenbeeck et al, 2007 ), leucine-rich repeat kinase 1 ( LRRK1 ) and melanocyte-inducing transcription factor ( MITF ) genes ( Howaldt et al, 2020 ; Iida et al, 2016 ; Lu et al, 2014 ). The pathogenesis of these forms is poorly characterized due to the small number of identified patients.…”
Section: Pathogenesis Of Aromentioning
confidence: 99%
“…Recent structural work reveals that the C-terminal 28 residues of LRRK2 form an elongated a-helix that extends along the entire kinase domain, interacting with both its C-and N-lobes that likely stabilize the kinase domain and may form binding platforms for other LRRK2 regulators [59]. Several autosomal recessive variants that induce frameshift or truncating mutations impact the equivalent C-terminal residues of LRRK1 and cause OSMD [6][7][8][9]. We have found that one of these mutations, namely E1980A-FS, impacts the C-terminal 66 residues and inactivates LRRK1 ( Fig 5D).…”
Section: Recent Structural Work Indicates That the Kinase Domain Of Wmentioning
confidence: 99%
“…Genetic evidence in humans, points towards LRRK1 regulating bone biology and LRRK2 contributing to Parkinson's disease. Autosomal recessive variants that induce frameshift or truncating mutations within the Cterminal domain of LRRK1, that are likely loss of function, cause a severe metabolic bone disorder termed osteosclerotic metaphyseal dysplasia (OSMD) [6][7][8][9]. This is a unique form of osteopetrosis characterized by severe osteosclerosis localized to the metaphyses of long bones [10].…”
Section: Introductionmentioning
confidence: 99%